ANALYSIS OF THE EFFECT OF COMPRESSIVE STRENGTH OF MORTAR USINGCANE WASTE ASH AND LIME - Mulyadi, Asri; Saloma, Saloma; Nurjanah, Siti Aisyah (Rang Teknik Journal, 2025)
From the results of research and testing of mortar with a variety of bagasse ash mixtures as a substitute for fine aggregate and limestone, it can be concluded that the compressive strength of normal mortar without bagasse ash waste but using limestone water is 1.90 kg/cm2, the compressive strength of mortar with Bagasse ash waste is 6% of the weight of cement and limestone is 2.29 kg/cm2 which is the optimum mixture content in this mixture. The compressive strength of mortar with sugarcane bagasse ash waste is 9% of the weight of cement and limestone has a compressive strength of 2.08 kg /cm2, the compressive strength of mortar with bagasse ash waste is 12% of the cement weight, the compressive strength is 2.12 kg/cm2, mortar mixed with bagasse ash and limestone will increase compared to normal mortar. Keywords: Aggregate, Cement, Compressive strength, Limestone, Compressive strength, Mortar, Sugarcane bagasse ash